Acute effects of optimal power load flywheel half-squat training on lower limb explosive power under different load volumes - Qi,Haonan; Hao,Mushuai; Qu,Boyang; Zhao,Liang; Han,Wei (PeerJ, 2025)
Background To explore the effects of flywheel half-squat interventions with different volumes of optimal power load (OPL) on post-activation performance enhancement (PAPE) in countermovement jump (CMJ) height and 30 m sprint performance among collegiate athletes. Methods A randomized crossover design was employed, recruiting 20 collegiate athletes to participate in the experiment. After determining each participant’s OPL, four different training load schemes were arranged for eight formal experiments, including four CMJ tests and four 30 m sprint tests. The differences between baseline and post-intervention at 0, 4, 8, and 12 min were compared. A two-factor repeated measures ANOVA was used for data analysis, with a significance level set at P < 0.05, and Cohen’s d value was used to represent the effect size (ES). Results (1) The improvement in CMJ height for different flywheel half-squat load volumes peaked at 8 min of recovery. In terms of ES, the improvement was Group B > Group C > Group A. (2) The improvement in 30 m sprint speed for Group A peaked at 4 min post-intervention, while the improvement for Groups B and C peaked at 8 min post-intervention. In terms of ES, the improvement was Group B > Group C > Group A. Conclusion Using two sets × six repetitions of OPL flywheel half-squat arrangement can induce a more reliable PAPE effect compared to higher load volumes. However, when using half-squats as a pre-stimulation exercise, the PAPE effect on CMJ height is superior to that on 30 m sprint speed.
Keywords: Flywheel training; Load volume; Optimal power load; Lower limb explosive power; Post-activation performance enhancement